Cocoa pod husks as precursors for biosynthesis of carbon dots as potential bioimaging tool - Norman, Ashreen; Mohd Jaaffar, Ahmad Kamil; Jamaludin, Nazzatush Shimar; Shirosaki, Yuki; Saad, Norazalina; Che Abdullah, Che Azurahanim (Iranian Nanotechnology Society, 2022)
Recent zero-dimensional carbon dots (CDs) have dominated the world of nanomaterials due to their ease of synthesis and nature of their precursors. The aim of this study is to synthesize, characterize and evaluate cytotoxicity of CDs from agricultural waste CPH for its potential use in the bioimaging field. The TEM analysis and particle size distribution curve revealed that the particles had a diameter of 10-30 nm, sphere-shaped and exhibited lattice fringes with a d-spacing of 0.196 nm. XRD analysis revealed a broad peak at 2Ɵ = 20.71°, indicating the existence of carbon. FTIR confirmed the presence of multiple functional chemical groups on the surface of the CPH CDs consist of C=O, N–H, C–N, and C–O–C. Due to the electronic transition’s characteristic of CDs, the UV-Vis absorption spectrum revealed two distinct peaks at 235 and 293 nm. PL spectra of CPH CDs revealed a red shift in the emission peak from 400 to 410 nm as the excitation wavelength increased from 320 to 380 nm. We used brine shrimp and human colon adenocarcinoma cells (Caco2) in vitro to determine the cytotoxicity of CPH CDs. In terms of brine shrimp assay, we found that 0.001 mg/ml showed lower lethality percentage with 57.93 ± 9.77 %. The cytotoxicity of CPH CDs was assessed in vitro using the MTT assay and Caco2 cell line's viability decreased with increasing concentration (IC50 = 155 ug/ml). Due to their favorable properties and low cytotoxicity, CPH CDs have the potential to be used as bioimaging tools.